2017
DOI: 10.1002/14651858.cd002768.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Physical exercise training for cystic fibrosis

Abstract: Analysis 1.1. Comparison 1 Aerobic training versus no physical training, Outcome 1 Change in VO2 peak during maximal exercise (ml/min per kg BW

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
93
0
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 121 publications
(103 citation statements)
references
References 83 publications
3
93
0
7
Order By: Relevance
“…Nixon et al administered the Kriska's Modifiable Activity Questionnaire (MAQ) to 30 CF patients and 30 healthy controls aged 7–17 years to assess physical activity over the previous year. While mean total hours of physical activity per week and the relative intensity of physical activity expressed as MET‐h · week were similar in both groups, the time per week spent in vigorous activities was significantly lower in the CF patients . Using questions from the Centers for Disease Control's Youth Risk Behavior Survey (YRBS), Britto et al found no differences between CF patients aged 12–19 years and their matched peers in the participation in the following three types of activities: team sports, physical education classes, and the number of activities per week that “make you sweat or breathe hard.” Younger CF adolescents were more likely to participate in all three types activities when adjusted for gender and health status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nixon et al administered the Kriska's Modifiable Activity Questionnaire (MAQ) to 30 CF patients and 30 healthy controls aged 7–17 years to assess physical activity over the previous year. While mean total hours of physical activity per week and the relative intensity of physical activity expressed as MET‐h · week were similar in both groups, the time per week spent in vigorous activities was significantly lower in the CF patients . Using questions from the Centers for Disease Control's Youth Risk Behavior Survey (YRBS), Britto et al found no differences between CF patients aged 12–19 years and their matched peers in the participation in the following three types of activities: team sports, physical education classes, and the number of activities per week that “make you sweat or breathe hard.” Younger CF adolescents were more likely to participate in all three types activities when adjusted for gender and health status.…”
Section: Discussionmentioning
confidence: 99%
“…Exercise and habitual physical activity (HPA) are important components in the care of patients with cystic fibrosis (CF) . A high level of physical activity may lead to improved airway clearance by increasing trans‐epithelial fluid transport, vibration, and raised ventilation and may reduce or even prevent lung function decline …”
Section: Introductionmentioning
confidence: 99%
“…Strategies to combine effective interventions to minimise treatment time are needed. Exercise improves physical fitness and may also improve lung function and quality of life in people with CF [5]. If exercise also aids mucus clearance, it would reduce treatment time, as exercise could substitute airway clearance interventions, while gaining the other known benefits of exercise.…”
Section: Introductionmentioning
confidence: 99%
“…The life expectancy of people with cystic fibrosis (CF) has increased dramatically over the last three decades with a growing armamentarium of pharmacologic and non‐pharmacologic interventions that positively impact health outcomes. Exercise training is one non‐pharmacologic intervention that is a recommended adjunctive form of airway clearance and has been shown to have many promising health outcomes including improved exercise capacity (EC), improved or reduced rate of decline in lung function, and improved quality of life in children and adolescents with CF. Regular exercise training can increase EC and many studies have demonstrated that higher EC is associated with favorable health outcomes such as greater life expectancy, decreased inflammation (IgG levels), increased bone mineral density, reduced hospitalizations due to pulmonary exacerbation, and improved quality of life in children and adolescents with CF.…”
Section: Introductionmentioning
confidence: 99%